Chemical Modification of the sp‐Hybridized Carbon Atoms of Graphdiyne by Using Organic Sulfur. Issue 22 (15th March 2019) - Yang, Ze; Cui, Weiwei; Wang, Kun; Song, Yuwei; Zhao, Fuhua; Wang, Ning; Long, Yunze; Wang, Huanlei; Huang, Changshui
Abstract: Invited for the cover of this issue is the group of Changshui Huang and co‐workers at the Qingdao Institute of Bioenergy and Bioprocess Technology, Chinese Academy of Sciences. The image depicts sulfur‐decorated graphdiyne, which can provide more defects and storage sites, thus displaying good performance for energy storage devices. Read the full text of the article at 10.1002/chem.201900477 . Abstract : " The as‐prepared S modified GDY possesses numerous heteroatom defects and active sites, which is crucial for the excellent performance of energy storage devices such as lithium ion batteries " Read more about the story behind the cover in the Cover Profile and about the research itself on page 5643 ff. (DOI: 10.1002/chem.201900477 ).